Performance analysis of SMI filter for antenna array receiver in pulse interference environment - Wang, Jie; Ou, Gang; Liu, Wenxiang; Lu, Zukun; Yin, Haibo (Frontiers in Physics, 2023)
This paper analyzes the performance of sample matrix inversion (SMI) filter used by antenna array receivers in pulse interference environment. Firstly, from the perspective of comparison, it is proved that the theoretical optimal signal to interference noise ratio (SINR) of SMI filter under pulse interference is the same with that under continuous interferences. Then the convergence characteristics of SMI filter under pulse interference are deduced, and the relationship between the convergence speed and length of training samples and duty of interferences is given. Finally, the results of signal simulation are consistent with those of numerical analysis, which verifies the correctness of theoretical analysis. The results show that the convergence speed of SMI filter decreases under pulse interference, and the SMI filter needs more training samples to suppress the pulse interference effectively.